Molecular detection of Mycobacterium tuberculosis and its relationship to histopathological diagnosis in paraffin-embedded lymph node tissues - Nourein, Ihab Hamed; Ahmed, Hussain Gadelkarim; Hassan, Hassan Elsiddig; Elmubasher, Maysa Badawi; din, Sara Abul Gasim Seif el; Elbadri, Moawia Ahmed; Shoaib, Omer Mohammed; Mustafa, Saadalnour Abusail (International Journal of Research in Medical Sciences, 2016)
Background: Tuberculous lymphadenitis (TBL) is one of the most common forms of extra pulmonary tuberculosis (EPTB) worldwide, with difficulty in its diagnosis. And since in the Sudan, the routinely used method for diagnosis is conventional histopathology, the aim of this study was to confirm the histopathological diagnosis by polymerase chain reaction (PCR). Methods: In this study 718 lymph node (LN) biopsies were retrieved, of which 161 were diagnosed as TBL (histopathological evidences). PCR technique was performed for all 161 positive samples to detect the IS6110 sequence of M. tuberculosis as well as to obtain the sensitivity and specificity of morphological diagnosis. Results: Out of 161 specimens 135 (84%) were found to be positive with PCR, the remaining 26 (16%) were negative. Conclusions: Although PCR indicated high sensitivity it can’t be a substitute for conventional histopathology in the diagnosis of tuberculous lymphadenitis in tissue.